Is the Accounting Profession serving Public Interest or Capital Interest? - Dr. Chesoli. J W (IJRDO - Journal of Business Management, 2019)
As an integral facet of society, the accounting profession has a role in the State and the corporate sector, and is also expected to serve the public interest. The capacity for the Kenyan accounting profession to serve the public interest is considered in the context of legislation and the accounting standard setting process. Specific reference is made to the Kenya Accountants Act cap 531 No. 15 of 2008 and IFRS Application in Kenya. It is argued that the combined effect of these Acts is to legislate bias so that accounting standards privilege the specific needs of holders of capital that is capital interest. The assumption that capital markets are surrogate for the public interest is contested. Accordingly, if the accounting profession follows national objectives to support capital markets, it may undermine its role in serving society.